X-ray and Neutron Techniques for Nanomaterials Characterization - Kumar, Challa S.S.R (Springer Berlin Heidelberg : Imprint: Springer, 2016)
Fifth volume of a 40 volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about X-ray and Neutron Techniques for Nanomaterials Characterization. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.